CENTRAL GOVERNMENT REPORTING QUALITY IN LHOKSEUMAWE KPPN PARTNERS WORKING UNIT - Ayu Harisa; Puji Wibowo (Polytechnic of State Finance STAN, 2023)
This study aims to examine determinants of financial statements quality of central government institutions. There was a change in the implementation of full accrual-based accounting in the Indonesian government in 2015, with an impact on the quality of government financial reporting. This study is a development of previous research using four exogenous determinants, namely organizational commitments, human resources competencies, internal control systems, and the implementation of accrual-based accounting. The testing method employed in this research is quantitative. This research uses a questionnaire as a tool to collect data from respondents. The population in this study was the partner institutions in the State Treasury Office (KPPN) Lhokseumawe. The sample that can be used in this research is 93 respondents. The partial Least Square (PLS) technique was used to analyze data processed using Smart PLS 3.0. The results show that organizational commitment, internal control systems, and the implementation of accrual-based accounting have positive and significant impacts on the financial statements quality of central government institutions. Meanwhile, human resources competencies does not affect government reporting quality